PETROLOGICAL DIVERSITY AND ORIGIN OF OPHIOLITES IN JAPAN AND FAR EAST RUSSIA WITH EMPHASIS ON DEPLETED HARZBURGITE - Ishiwatari A.; Sokolov S.D.; Vysotskiy S.V. (My University, 2004)
Ophiolites are divided into lherzolite-type (L-type) and harzburgite-type (H-type) by the lithology of their mantle peridotites. Rare depleted harzburgite-type (DH-type) is distinguished from the normal H-type by the more refractory nature of its mantle peridotite and the occurrence of orthopyroxene-type cumulate rocks including iron-rich harzburgite and orthopyroxenite. The Shelting (Sakhalin) and Krasnaya (Koryak Mountains) ophiolites in Far East Russia, which have both depleted harzburgite and orthopyroxene-type cumulate rocks, belong to this newly defined DH-type. The ophiolites in SW Japan-Primorye, NE Japan-Sakhalin, and the Koryak Mountains in the northwestern Pacific margin have diverse ophiolite types ranging from L- to DH-types. The wide petrological diversity, the common occurrence of DH-type, and the presence of thick crustal sections in these ophiolites suggest regionally inhomogeneous, commonly very high degrees of mantle melting over subduction zones, as in the modem Mariana forearc environment. The ophiolites of Japan and Far East Russia range in age from Early Palaeozoic to Cenozoic and are tectonically underlain by younger blueschists and accretionary complexes. The spatial association of these ophiolites with blueschists is analogous to the ophiolite-blueschist assemblages recovered from the Mariana forearc. This association might have formed in a period of non-accretion at an oceanic subduction zone that was followed by voluminous accretion of sediments, facilitating subsequent uplift of the ophiolites and blueschists.